Happy marriage?! 7 - Enjoji, Maki; Thistlethwaite, Nancy (Shojo beat manga., 2014)
"Chiwa Takanashi has married a total stranger--company president Hokuto Mamiya--to get her father out of debt. Hokuto is working harder than ever after his promotion, and the couple rarely spends time together anymore. Chiwa continues working at Ai-Max with Asahina, a guy she dated in college. Asahina knows she's married to Hokuto, but he still has feelings for Chiwa."--Back cover.